Flora of Espírito Santo: Lentibulariaceae - Guedes, Felipe Martins; Miranda, Vitor Fernandes Oliveira [UNESP]; Alves, Marccus (FapUNIFESP (SciELO), 2022)
The present study comprises the taxonomic treatment of the Lentibulariaceae species in Espírito Santo state, as a continuation of a series of studies focused on the Flora of Espírito Santo. Herein we present an identification key, morphological descriptions, illustrations, distribution map, list of analysed material and comments about taxonomy and distribution of the species. We confirmed the occurrence of 16 species in Espírito Santo state, of which four are new records and only three are not found in protected areas.
Keywords: carnivorous plants; Flora of Brazil 2020; Genlisea; taxonomy; Utricularia